Self-Organized One-Dimensional TiO2 Nanotube/Nanowire Array Films for Use in Excitonic Solar Cells: A Review - Ningzhong Bao; Xinjian Feng; Craig A. Grimes (Journal of Nanotechnology)
We review the use of self-assembled, vertically oriented one-dimensional (1D) titania nanowire and nanotube geometries in several third-generation excitonic solar cell designs including those based upon bulk heterojunction, ordered heterojunction, Förster resonance energy transfer (FRET), and liquid-junction dye-sensitized solar cells (DSSCs).